Efektifitas Media Game “Handwash” dalam Meningkatkan Kemampuan Praktek Cuci Tangan Pada Anak Sekolah Dasar - Wulan Septiana Putri; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is being conducted to find out about the effectiveness of Handwash game as a media to increase the ability of elementary students in the practice of washing hands. The connectivity theory stated that the more complex a knowledge is the more retainable and accessible it is. The sampling methods in this research is using quota sampling technique with random sampling. The population in this research is the elementary students of SD Kanigoro of the grade 4 and 5 with the total of 40 students. Based on the hypothesis test that is being conducted using statistic test of non parametric mcNemar. There is effectiveness of game Handwash on increasing the ability of elementary student to perform hand washing. This is shown by the calculation by the statistic test non parametric mcNemar to the independent variable game Handwash (X) towards the dependent variable the ability to perform hand washing (Y), it is being obtain from the test the rate of 0.002 significance number of which is less than 0.05 which means that there is an effectiveness of variable X towards variable Y. The recommendation given is that the teacher in SD Kanigoro is expected to use the result of this study as a consideration in order to get the maximum result of learning process.